Performance analysis of single slope solar still integrated with refrigeration systems. Issue 1 (April 2021) - Aneesh, V; Vishnu, S; Das, Arun P; Ajith, M S
Abstract: The over misuse of existing new water supplies has become a major issue in numerous pieces of the world. Hence, recycling of water is necessary to meet the requirements of the growing population. Solar water purification is one of the viable technologies. This work is focused on the productivity enhancement of a single slope solar still by using two types of refrigeration system such as thermoelectric refrigeration system and vapour compression refrigeration system. In the modification of the existing solar still setup, the extra cooling was achieved by adding thermoelectric modules in the external condenser which is used for increasing the condensation area and thus the rate of evaporation. In the second set up, a vapour compression refrigeration system is coupled with the solar still in such a way that the evaporator coil of the refrigeration system is placed inside the external condenser for providing extra cooling effect and the condenser of the refrigeration system is placed in the basin of solar still for enhancing evaporation rate of the basin water. The results show that these modifications enhanced the performance and productivity of the solar still. The enhancement in the productivity of the passive solar still using thermoelectric refrigeration system was found to be 45.77% more and for solar still with external condenser integrated with vapor compression refrigeration system was found to be 167.7% more as compared with the solar still alone.